PERAN UMKM DALAM MENDORONG PERTUMBUHAN EKONOMI DI ERA DIGITAL - Anugrah Permana Tanjung; Imam Syuhada; Rayhan Tambak Bintang (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Miniaturized scale, Little and Medium Endeavors (MSMEs) play an critical part in driving financial development, especially in the digital era. Digital transformation provides great opportunities for MSMEs to increase operational efficiency, expand markets and compete at a global level. Digitalization allows MSMEs to utilize technology such as e-commerce, social media and fintech to increase access to consumers and financial resources. In addition, the adoption of digital technology helps MSMEs in product innovation, supply chain management and marketing strategies. However, challenges such as digital literacy, limited infrastructure and access to technology are still obstacles for some MSMEs. Therefore, support is needed from the government and the private sector in providing training, access to digital infrastructure, and conducive policies. With a supporting ecosystem, MSMEs can play a more significant role in creating jobs, increasing competitiveness, and encouraging inclusive economic growth in the digital era.